ALTERNATIF PEMBIAYAAN INFRASTRUKTUR PERKOTAAN: KAJIAN TERHADAP MEKANISME DEVELOPER`S CONTRIBUTION DI DKI JAKARTA - Suparto, Jessica Dorothy; Fahmi, Erwin (Universitas Tarumanagara, 2024)
Innovation in urban financing in DKI Jakarta needs to be continuously improved, considering that conventional financial sources, such as local and national government budget (APBD and APBN), are limited vis a vis the increasing demand. Mechanisms such as Public-Private Partnership (PPP or KPBU) which are currently being put forward, although they address the issue of efficiency, have not yet addressed another issue, namely the issue of equity. Parties that impose additional burden on infrastructure do not cover the financing burden proportionally. The mechanism that has been developed in the state of New South Wales - Australia, namely the developer’ contribution mechanism, has embryonic-ally been introduced in DKI Jakarta through the Governor’ Regulation (Pergub) No. 175 year 2015 concerning the imposition of compensation for exceeding the building floor coefficient value, which has been amended by the Pergub No. 210 of 2016 concerning the same. This study aims at investigating the similarities and differences between the Pergub and the developer’s contribution mechanism, the depthness, and steps that can be taken to develop the application of the mechanism in DKI Jakarta. For those purposes, the study uses a qualitative research approach. Data collection is mainly carried out by field observations, and interviews with developers, local government officials, and related parties. The analysis uses chronology, comparison, and interpretation methods. Findings of the study demontrate that the mechanism is applicable based on efficiency and equity arguments. In addition, this mechanism is also justified on the bases of current implementation experiences. However, for such an application, a number of aspects need to be fulfilled, namely the clear nexus between the infrastructure built and the advantages of KLB, expanding the scope of the policy, and a stronger policy umbrella, namely Provincial Regulation (Perda) instead of Government’ Regulation. Keywords: Inovation; Urban Financing; Efficiency and Equity; DKI Jakarta Abstrak Inovasi pembiayaan infrastruktur perkotaan di DKI Jakarta perlu terus ditingkatkan, mengingat sumber-sumber pembiayaan konvensional, seperti APBD dan APBN, semakin terbatas di hadapan kebutuhan yang meningkat. Mekanisme seperti Kerjasama Pemerintah – Badan Usaha (KPBU, atau public-private partnership [PPP]) yang sekarang diketengahkan, meskipun menjawab persoalan efisiensi, namun belum menjawab isu lain, yakni persoalan keadilan/ekuiti. Pihak yang memberikan beban tambahan pada infrastruktur tidak menanggung beban pembiayaan yang proporsional. Mekanisme yang berkembang di negara bagian New South Wales - Australia, yakni mekanisme developer’s contribution, secara embrionik telah diintroduksikan di DKI Jakarta melalui Peraturan Gubernur (Pergub) DKI Jakarta No 175 Tahun 2015 tentang Pengenaan Kompensasi terhadap Pelampauan Nilai Koefisien Lantai Bangunan, yang telah diperbaharui menjadi Pergub No 210 Tahun 2016 tentang hal yang sama. Studi ini bertujuan mengkaji kesamaan dan perbedaan Pergub dan mekanisme developer’s contribution, kedalaman, dan langkah-langkah yang dapat dilakukan untuk mengembangkan penerapan mekanisme tersebut di DKI Jakarta. Untuk itu, digunakan pendekatan penelitian kualitatif, dengan melakukan observasi lapangan, dan wawancara mendalam dengan pengembang, Pemerintah Daerah, dan pihak-pihak terkait. Analisis menggunakan metode kronologi, pembandingan, dan interpretasi. Hasil penelitian menunjukkan kelayakan mekanisme ini diterapkan secara penuh berdasarkan argumentasi efisiensi dan ekuiti. Selain itu, mekanisme ini dijustifikasi berdasarkan pengalaman penerapannya selama ini. Namun, untuk itu sejumlah hal juga perlu dipenuhi, antara lain menguatkan kaitan (nexus) antara infrastruktur yang dibangun dan kelebihan KLB, diperluasnya cakupan kebijakan, dan diperkuatnya payung hukum kebijakan dimaksud.